RELATIONSHIP OF ULTRA-PROCESSED FOOD CONSUMPTION AND PHYSICAL ACTIVITY WITH OVER-NUTRITION STATUS AMONG STUDENTS AT SMAN 1 JEMBER - Daniswara, Carissa Fawwaz; Andrias, Dini Ririn; Rifqi , Mahmud Aditya; Nirmala, Intan Ria (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Over-nutrition among Indonesian adolescents has increased significantly over the past decade. High consumption of ultra-processed foods (UPFs) and low physical activity are the primary contributing risk factors. Adolescents are particularly vulnerable to changes in dietary patterns and lifestyle that may affect long-term health outcomes. This study aimed to analyze the relationship between UPF consumption and physical activity with over-nutrition status among students at SMAN 1 Jember. A cross-sectional design was employed involving 89 students from grades X and XI, selected through purposive sampling. Data were collected using the SQ-FFQ and IPAQ. Nutritional status was determined based on BMI-for-age, following the standards of the Indonesian Ministry of Health. Statistical analysis was conducted using the chi-square test with a significance level of p<0.05. The results showed that the majority of respondents were not over-nutrition (76.4%), while 14.6% were classified as over-nutrition. A significant association was found between the frequency of UPF consumption and over-nutrition status (p=0.001). However, no significant association was observed between physical activity and over-nutrition status (p=0.797). These findings add evidence for further research on high UPF consumption on increased risk of over-nutrition in adolescents. In contrast, physical activity did not show a significant association, possibly due to the presence of other contributing factors.